2002
DOI: 10.1002/hed.10023
|View full text |Cite
|
Sign up to set email alerts
|

T stage as prognostic factor in irradiated localized squamous cell carcinoma of the nasal vestibule

Abstract: The effect of radiotherapy is significantly correlated with T stage (p =.0001) and hence less successful in T3 lesions as primary treatment option. The high incidence of second primary tumors in the lung is indicative for a similar carcinogenic influence of smoking on the nasal vestibule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 22 publications
2
44
1
7
Order By: Relevance
“…The incidence of reported positive nodes in SCCNV is depicted in Table I. [4][5][6]11,12,16,[18][19][20][21][22][23][24][25][26][27][28][29]31,34,35 CONCLUSION SCCNV cancer is an uncommon isolated form of cancer, possibly originating in the mucocutaneous junction and is usually smoking induced. The incidence of synchronous or delayed regional metastases is higher than 20% in about half of the reported series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of reported positive nodes in SCCNV is depicted in Table I. [4][5][6]11,12,16,[18][19][20][21][22][23][24][25][26][27][28][29]31,34,35 CONCLUSION SCCNV cancer is an uncommon isolated form of cancer, possibly originating in the mucocutaneous junction and is usually smoking induced. The incidence of synchronous or delayed regional metastases is higher than 20% in about half of the reported series.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Direct insult of tobacco smoke on nasal mucosa in the region of the mucocutaneous junction is a reasonable hypothesis that may well explain the increased incidence of nasal cancer in smokers, suggested or reported. In a previous report, we found 9 of 11 patients with SCCNV to be exposed to cigarette smoke with a history of a mean of 103 pack-years.…”
mentioning
confidence: 96%
“…They display a natural history similar to that of skin cancers and their prognosis is more favorable compared with other cancers of the nasal cavity (9). Nasal vestibular carcinomas are often located in the nasal floor, the nasal dome, the medial crus of the lower lateral cartilage and the inner lining of the alar wing (lateral crus), and account for <3.8% of all nasal mucosal tumors and 1% of all malignant tumors of the head and neck (10)(11)(12). Human papillomavirus infection and smoking are considered to be risk factors (12).…”
Section: Discussionmentioning
confidence: 99%
“…Jeannon et al [10] reported that patients with Wang T1 tumors had a 5-year overall survival of 72 %, compared with 45 % for those with T2 and 32 % with those with T3 (p = 0.0098). Kummer et al [2] reported that all of three patients with tumors classified as T3 according to the Wang system died from the disease (2, local; 1, distant). Agger et al reported that T2 and T3 Wang tumors had poor prognoses, with a 5-year disease-specific survival of 63 and 39 % and an overall survival of 43 and 0 %, respectively [1].…”
Section: Discussionmentioning
confidence: 99%
“…Agger et al reported the annual incidence as 0.32 per 100,000 habitants in Denmark [1]. However, it has a significant impact on the quality of life, even in early localized disease, when treated surgically [2]. Therefore, despite the existing belief that more advanced tumors are best treated with primary surgery and radiotherapy, radiotherapy is often given instead of surgery [3].…”
Section: Introductionmentioning
confidence: 99%